1925 Ind. Acts 495, § 2-3 - (:unkn) unknown (My University, 1925)
Enhanced the sentence of anyone who committed a crime with a pistol or revolver without a license to carry. Violators guilty of a felony, imprisoned not less than one nor more than five years.
Keywords: CARRY - INTENT TO COMMIT CRIME